MENINGKATKAN KONSENTRASI ANAK ATTENTION DEFICIT HYPERACTIVITY DISOERDER (ADHD) MELALUI OLAHRAGA MEMANAH - Ania Susanti; Wiwin Suryaningsih (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
Attention Deficit Hyperactivity Disorder (ADHD) is a psychic term used to refer to behavioral disorders that have recently been found in children. Child development can be disrupted if a child is indicated with ADHD, both cognitive, social emotional and communication development. This study aims to determine whether archery exercise can improve the ability to concentrate ADHD children. In this study the subject of the study were three children who had been declared to have ADHD, aged 6 years. The type of research used is a single subject experimental design. Data collection method uses observation. Descriptive chart analysis was used to analyze the data in this study. Based on data analysis conducted, the results of the study describe that archery exercise can increase concentration in children with ADHD.